Bacterially synthesized tellurium nanostructures for broadband ultrafast nonlinear optical applications - Blau, Werner; Zhang, Hongzhou (My University, 2019)
Elementary tellurium is currently of great interest as an element with potential promise in nano-technology applications because of the recent discovery regarding its three two-dimensional phases and the existence of Weyl nodes around its Femi level. Here, we report on the unique nano-photonic properties of elemental tellurium particles [Te(0)], as harvest from a culture of a tellurium-oxyanion respiring bacteria. The bacterially-formed nano-crystals prove effective in the photonic applications tested compared to the chemically-formed nano-materials, suggesting a unique and environmentally friendly route of synthesis. Nonlinear optical measurements of this material reveal the strong saturable absorption and nonlinear optical extinctions induced by Mie scattering over broad temporal and wavelength ranges. In both cases, Te-nanoparticles exhibit superior optical nonlinearity compared to graphene. We demonstrate that biological tellurium can be used for a variety of photonic applications which include their proof-of-concept for employment as ultrafast mode-lockers and all-optical switches.
PUBLISHED
cited By 0
Keywords: Elementary tellurium; Nano-technology; Nano-photonic properties